Effects of chlorhexidine, ethylenediaminetetraacetic acid, and sodium hypochlorite on cell viability of human gingival fibroblasts in vitro - Abdel-Rahman Youssef; Ehdaa Alturkistani; Israa Muharrij; Lina Alsrehi; Noor Shafei; Nora Alzahrani; Mashael Alqahtani (Wolters Kluwer Medknow Publications, 2020)
Introduction: The aim of this in vitro study was to evaluate the cytotoxic effects of chlorhexidine (CHX), ethylenediaminetetraacetic acid (EDTA), and sodium hypochlorite (NaOCl) irrigants on human gingival fibroblasts. Materials and Methods: Gingival fibroblasts were cultured in Dulbecco Modified Eagle Medium for 24 h. Then, the cells were exposed for 1 min to different concentrations of CHX, EDTA, and NaOCl and the cell viability was assessed using 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide tetrazolium reduction assay. The percentage of gingival fibroblast viability was compared to control (100% viability). Results: All concentrations of CHX, EDTA, and NaOCl were cytotoxic to gingival fibroblasts compared to control group and this effect was dose-dependent (P < 0.0001). There was an inverse relationship between the concentrations of these irrigants and cell viability. The highest clinically used concentrations of CHX (2%), EDTA (17%) and NaOCl (2.5%) reduced the cell viability to 2.2%, 3.2%, and 1.9%, respectively, compared to the 100% viability of control. However, the lowest concentration of CHX (0.00002%), EDTA (0.00017%), and NaOCl (0.000025%) increased the cell viability to 39.8%, 30.2%, and 44.2%, respectively, in comparison to control. There were no significant differences between the irrigants at clinically used concentrations (P > 0.05). Conclusion: The cytotoxic effect of CHX, EDTA, and NaOCl on gingival fibroblasts was dose-dependent. Further studies are needed to assess and optimize the safety and efficacy of these irrigants in vivo.